Análisis de los sistemas de comercialización informal de productos agrícolas en la vía San Carlos – Zapotal de la Provincia de Los Ríos. - Macías Herrera, Liliana Estefanía (2019)
On the San Carlos - Zapotal road, there are a large number of sellers of agricultural products, who see this activity as their main income for family support. Considering the above, this research aimed to analyze the commercialization systems of agricultural products on the San Carlos - Zapotal road in the province of Los Ríos. The study took place in the area between the San Carlos parish and the Zapotal enclosure, in the province of Los Ríos. 25 informal sellers of agricultural products from that area were surveyed. The results obtained show that, in the study area of the total number of vendors, 13 sell bananas, 10 sell orange, tangerine, banana and coconut, 8 sell pineapple and watermelon, 4 avocado and grapefruit, and 3 papaya, which have more than 70% profitability, which demonstrates the viability of this activity. The products are stored by 56% of the sellers at the sales site, evidencing that 72% apply only the washing as a treatment before storing the products that 92% sell them both at the premises and approaching the vehicle both to the consumer as intermediaries as a whole. The investment of fruit sellers is $ 651.00 to $ 800.00 per month, obtaining a profit of $ 501.00 to $ 700.00, representing such income in most cases between 91 and 100% of total family income per month, leaving a savings of $ 100.00 to $ 300.00, so the family economy depends directly on this activity since none has an additional income. The sellers in 48% use an indirect marketing system, which is generally based on buying agricultural products from intermediaries, and then selling them to the general public, in this case taking their products to the cars that circulate on the road, of which, 60% sell whole and 40% chopped, lacking in 40% distinctive packaging and 40% added value, however, if a wash is provided, ignoring the rules for handling food for human consumption, hygiene and health, guaranteeing the food safety of consumers. Keywords: informal sale, agricultural products, agricultural marketing.